Wednesday

December 17, 2014

December 17, 2014

Posted by **Bre** on Friday, January 20, 2012 at 4:37pm.

3x+9y=48

-6x+y=56

- math -
**Steve**, Friday, January 20, 2012 at 11:51pmTo use the substitution method, you solve one equation for x, and then substitute that expression for x in the other equation. or, you can solve for y if it's easier.

3x + 9y = 48

3x = 48 - 97

x = 16 - 3y

-6x + y = 56

-6(16-3y) + y = 56

-96 + 19y = 56

19y = 152

y = 8

so,

x = 16 - 24 = -8

**Answer this Question**

**Related Questions**

Linear Equations - Can you please help solve this equation using the ...

math - solve by the substitution method. 5x + 7y= -19 x=4-4y what is the ...

math - Solve by substitution method 8x+9=-2 -9x+y=69 what is the solution of the...

math - Solve by substitution method 7m+n=27 m-8n=69 What is the solution of the ...

Math - Use the substitution method to solve the following system of linear ...

algebra - Requesting help. (I must reckon, that X is a variable, and y is y-...

math - solve by the substitution method 3x + 6y = 27 -2x + y = 12 what is the ...

Math - solve using the substitution method. If the system has no solution or ...

Substitution Method-Plz help - Use the Substitution method to solve the system ...

math - solve by the substitution method 3x + 6y = 27 -2x + y = 12 what is the ...